Antidoping programme and biological monitoring before and during the 2014 FIFA World Cup Brazil. Issue 9 (15th April 2015) - Baume, Norbert; Jan, Nicolas; Emery, Caroline; Mandanis, Béatrice; Schweizer, Carine; Giraud, Sylvain; Leuenberger, Nicolas; Marclay, François; Nicoli, Raul; Perrenoud, Laurent; Robinson, Neil; Dvorak, Jiri; et al.
Abstract : Background: The FIFA has implemented an important antidoping programme for the 2014 FIFA World Cup. Aim: To perform the analyses before and during the World Cup with biological monitoring of blood and urine samples. Methods: All qualified players from the 32 teams participating in the World Cup were tested out-of-competition. During the World Cup, 2–8 players per match were tested. Over 1000 samples were collected in total and analysed in the WADA accredited Laboratory of Lausanne. Results: The quality of the analyses was at the required level as described in the WADA technical documents. The urinary steroid profiles of the players were stable and consistent with previously published papers on football players. During the competition, amphetamine was detected in a sample collected on a player who had a therapeutic use exemption for attention deficit hyperactivity disorder. The blood passport data showed no significant difference in haemoglobin values between out-of-competition and postmatch samples. Conclusions: Logistical issues linked to biological samples collection, and the overseas shipment during the World Cup did not impair the quality of the analyses, especially when used as the biological passport of football players.